Pengaruh Current Ratio, Net Profit Margin, dan Ukuran Perusahaan terhadap Nilai Perusahaan Sektor Aneka Industri pada Index Saham Syariah Indonesia - Febi Novita Sari; Tony Iswadi; Maisya Pratiwi (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2026)
This study aims to determine the effect of Current Ratio, Net Profit Margin, and company size on company value (manufacturing companies in the miscellaneous industry sector of the Indonesian Sharia Stock Index 2020-2024). The data used in this study are financial reports available on the Indonesia Stock Exchange (IDX). The sample was determined using purposive sampling, with 26 companies selected from 20 companies that met the criteria for analysis using panel data regression analysis with the assistance of Eviews 13. The results found that the Current Ratio and Net Profit Margin had no significant partial effect on company value, while company size had a positive and significant partial effect on company value. The Current Ratio, Net Profit Margin, and company size simultaneously have a significant effect on company value.